Improving the Mechanical Properties of GPLs-SiAlON Composites by Microfluidization Technique as a New Approach to Dispersion of GPLs - SİNEM BAŞKUT; Servet TURAN (Gazi Üniversitesi Fen Bilimleri Dergisi, 2022)
Graphene platelets (GPLs) are frequently preferred as reinforcement material to improve the mechanical properties of many advanced technology ceramics, thanks to their superior properties. However, their reinforcement levels vary depending on whether they are homogeneously distributed in the matrix microstructure. This is generally controlled by the thickness (number of layers) of the GPLs. In general, single- or few-layer GPLs show high performance as reinforcement but are commercially expensive. This limits their large-scale use. This study aims to achieve the performance of the GPLs (GPLRef), which is determined to have a high mechanical reinforcement level but is quite expensive, by economically thinning other GPLs (C0-GPL) with similar platelet size but cheaper and thicker structure. For this purpose, the microfluidization technique, a new approach to the dispersion of GPLs, was applied. C0-GPL is exposed to 1, 2, 4 and 8 cycles of microfluidization process. Microfluidized GPLs were added to the SiAlON matrix at a ratio of 1.5 wt %, and the GPLs-SiAlON composites were sintered using the spark plasma sintering (SPS) technique. The platelet size of C0-GPL decreased as the number of applied microfluidization cycles increased. However, while this reduction in platelet size was not significant up to 2 cycles, it was very pronounced at 4 and 8 cycles. Raman analyses revealed that GPLs could be dispersed effectively for up to 4 cycles. After this point, the GPLs fragmented rather than thin as the number of cycles increased. GPLs slightly thinner than GPLRef could be obtained with 2 cycles of microfluidization (C2-GPL). Therefore, C2-GPL were more homogeneously dispersed in SiAlON matrix microstructure compared to GPLRef. As a result, both the through-plane and in-plane direction fracture toughness values of SiAlON matrix containing C2-GPL, which partially preserved the platelet size, were higher than those of GPLRef-SiAlON. The fracture toughness of SiAlON matrix composites containing 4 and 8 cycles of microfluidized GPLs were lower than that of GPLRef-SiAlON as an adverse effect of decreasing platelet size. It has been determined that the mechanical reinforcement performance of commercially expensive GPLRef can be achieved economically by applying 2 cycles of microfluidization to cost-effective C0-GPL.